Variation of Helicoverpa armigera symbionts across developmental stages and geographic locations - Zhao, Chenchen; Wang, Li; Zhang, Kaixin; Zhu, Xiangzhen; Li, Dongyang; Ji, Jichao; Luo, Junyu; Cui, Jinjie (Frontiers in Microbiology, 2023)
Cotton bollworm Helicoverpa armigera poses a global problem, causing substantial economic and ecological losses. Endosymbionts in insects play crucial roles in multiple insect biological processes. However, the interactions between H. armigera and its symbionts have not been well characterized to date. We investigated the symbionts of the H. armigera in the whole life cycle from different geographical locations. In the whole life cycle of H. armigera, Proteobacteria, Firmicutes, Bacteroidetes, and Actinobacteria were the dominant bacteria at the phylum level, while Enterococcus, Enterobacter, Glutamicibacter, and Bacillus were the four dominant bacteria at the genus level. Furthermore, high similarity in symbiotic bacterial community was observed in different stages of H. armigera, which were dominated by Enterococcus and Enterobacter. In fields, the dominant bacteria were Proteobacteria and Bacteroidetes, whereas, in the laboratory, the dominant bacteria were Proteobacteria.At the genus level, the dominant bacteria in cotton bollworm eggs of wild populations were Enterobacterium, Morganella, Lactococcus, Asaia, Apibacter, and Enterococcus, and the subdominant bacteria were Bartonella, Pseudomonas and Orbus. Moreover, the symbionts varied with geographical locations, and the closer the geographical distance, the more similar the microbial composition. Taken together, our study identifies and compares the symbiont variation along with geographical gradients and host development dynamic, and reveals the high flexibility of microbiome communities in H. armigera which probably benefits for the successful survival in complicated changing environment.